Pengaruh Media Scrapbook Terhadap Hasil Belajar Siswa Materi Kerajaan-Kerajaan di Nusantara Kelas IV Sekolah Dasar - Kholifah, Suci Nur; Andaryani, Eka Titi (Paedagogie, 2026)
This study aims to determine and analyze the effect of scrapbook media on student learning outcomes of the material of kingdoms in the archipelago of grade IV of Ciwuni 01 Kesugihan State Elementary School. This study applies a quantitative approach with a pre-experimental method using a one group pretest-posttest design. The subjects of the study were 30 grade IV B elementary school students who were determined as saturated samples. Data collection was carried out through interviews, observations, pretest-posttest. The data obtained were then analyzed using paired sample tests and N-Gain tests. The results showed an average pretest of 68,50 increased to 85,83 in the posttest. The results of the paired sample t-test of the study obtained a t-test value (-12.095) with a significance of 0,000 <0,05 and the N-Gain Test obtained an average of 59,69 "quite effective" with t count> t table, namely 12,095> 2,045, so it can be seen that Ha is accepted and H0 is rejected. This shows that scrapbook media has a significant and effective influence in improving the learning outcomes of fourth grade students of Ciwuni 01 Kesugihan Elementary School on the material of kingdoms in the archipelago.